Electrical Field Effect on Peri-Implant Osteogenesis: A Histologic and Histomorphometric Study - Giannunzio, Graciela Ana (2008)
PURPOSE: Tissue response to injury, as occurs during wound healing, is a well-organized biologic event. Both clinical and experimental studies have shown external electrical stimulation to enhance tissue repair. The effect of in situ electrical stimulation has been studied in experimental models of fracture healing, ostectomy, osteogenic distraction, and implants. The aim of the present study was to evaluate the effect of an electrical field on peri-implant wound healing, using an experimental model that involved placing a metallic laminar implant in rat tibia. MATERIALS: Forty male Wistar rats weighing approximately 100 g were used. A titanium laminar implant (6 x 1 x 0.1 mm3) (Implant Vel, Buenos Aires, Argentina) was inserted through the hole and placed in the medullary compartment. The tissues were then repositioned and sutured carefully. An electric field generator (ECCEL, DAM, Argentina) was used to deliver the electric stimulus. The electric field plate was placed on the skin of both hind limbs. In sham group, the animals were subjected to the same procedure without connecting the plate to the electric field generator. All the animals were killed by ether overdose at 15 days of postimplantation. The tibiae were resected, fixed in 20% formalin, radiographed, and processed for embedding in methyl methacrylate. The ground sections were stained with 1% toluidine blue. The following parameters were evaluated: peri-implant bone volume and percentage of osseointegration. Statistical analysis of the results was performed using ANOVA (P < 0.05). RESULTS: Application of external positive or negative electrical fields using the experimental model (post-titanium implant bone healing in rat tibia), under the conditions stated herein, was found to enhance peri-implant lamellar bone volume compared with sham-treated animals. CONCLUSION: The use of a device generating a positive/negative electrical field resulted in the presence of woven bone.